(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Obesity is one of the most prevalent health concerns among all age groups & populations worldwide, resulting into a significant increase in mortality and morbidity related to metabolic disorders. Targeting one or more enzymes involved in lipid metabolism can be selective for evaluation of anti obesity action of drug. The present study was aimed to evaluate in vitro anti obesity action by inhibiting pancreatic lipase & ᾳ amylase enzyme by various fractions of methanolic extract of aerial parts Fagonia cretica L. along with their phytochemical analysis. The n- hexane (HFFC), Chloroform (CFFC), Ethyl acetate (EAFFC), n-butanol (BFFC) & aqueous fractions (AQFFC) were prepared from methanolic extracts of F. cretica L & were analyzed for qualitative as well as quantitative phytochemical study using reported methods. The qualitative phytochemical studies of prepared extract & fractions showed presence of flavonoids, saponins, phenolics, alkaloids & carbohydrates. All the fractions were then examined for their in-vitro lipase inhibitory & ᾳ amylase inhibitory activities at a concentration level of 50, 100, 150 & 200µg/ml and their percentage inhibitory effects were reported. Among the analyzed samples, BFFC showed highest lipase inhibitory action i.e. 83.02 ± 2.47% as compared to other fractions. EAFFC showed significantly higher ᾳ amylase inhibitory action i.e. 80.22 ± 1.18% as compared to other fractions.